SEMANTIC ANALYSIS OF THE PROVERBS WITH PROPER NAMES IN ENGLISH (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The article examines English proverbs that include proper names to convey lessons or ideas quickly and effectively. It explains how these proverbs have both a literal meaning and a deeper, symbolic meaning, often drawn from cultural or historical contexts. The analysis highlights how these proverbs use memorable language to pass on wisdom, reflect societal values, and facilitate communication.